Virulence Genes Detection in Streptococcus uberis and Streptococcus dysgalactiae Isolated from Bovine Mastitis in Gujarat, India - Parasana, Dixit K; Javia, Bhavesh B; Barad, Dilipsinh B; Ghodasara, Sanjay N; Fefar, Dhaval T (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
One of the most expensive illnesses in the dairy sector is mastitis. Due to decreased milk production and increased treatment costs, it generates significant financial losses to the dairy industries. Streptococcus uberis and Streptococcus dysgalactiae are two common environmental bacteria which cause bovine mastitis and have several virulence factors that play major role in pathogenicity. The objective of this study was to detect some important virulence genes of S. uberis and S. dysgalactiae. Overall, sixteen S. uberis and ten S. dysgalactiae were isolated from 320 milk samples. The virulence genes hasC, gapC and sua were found in 50%, 100% and 81.25% isolates of the S. uberis, respectively, while in S. dysgalactiae isolates, napr and eno genes were found in 60% and 20% isolates, respectively. This work helps us to understand the virulence traits and mechanisms underlying how novel mastitis strains emerge in response to preventative and curative measures.